Statistical quantifiers for few-fermion’ systems - Pennini, Flavia Catalina (2018)
With reference to a simple (analytically solvable) model containing a few fermions, we show that statistical quantifiers, devised for large numbers of particles (and macroscopic bodies), surprisingly turn out to provide significant insights into the fermion-model characteristics. We find that statistical complexity can be assessed with the same criteria in large systems and in few-fermions ones.